High-Pressure and High-Temperature Dissolution of Titanium from Titanium and Aluminum Residues: A Comparative Study - Srecko Stopic; Duško Kostić; Elif Emil-Kaya; Emircan Uysal; Sebahattin Gürmen; Aleksandar Mitrašinović; Mitar Perušić; Bernd Friedrich (Surfaces)
This study presents a comparative analysis of titanium leaching from tionite (a byproduct of the titanium dioxide production process) and carbothermally reduced red mud (derived from aluminum residues). Tionites from the sulfate process and red mud residue are known for their environmental impacts due to their metal content and acidic/basic nature. This study explored leaching as a method to recover titanium and other metals under high-pressure and high-temperature conditions using sulfuric acid. Experiments were conducted in an autoclave with different parameter changes, like varying oxygen pressure, temperature, and reaction time to optimize metal extraction. The leaching efficiency of titanium was found to be higher in the carbothermal-reduced slag compared to tionite due to the altered mineral phases in the reduced material. XRD and SEM-EDS analyses confirmed the differing leaching behaviors, with titanium compounds in tionite showing greater resistance to dissolution. These findings highlight the importance of thermal pre-treatment for optimizing metal recovery from industrial residues. The main aim of this study is to contribute to the development of sustainable waste management solutions for tionites and red mud, emphasizing the potential of hydrometallurgical methods for metal recovery. The results are expected to inform future research and industrial applications, advancing the recovery of valuable metals while reducing the environmental footprint of titanium and aluminum residue disposal.